2004
DOI: 10.2165/00002018-200427130-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Unlicensed and Off-Label Drug Use on Adverse Drug Reactions in Paediatric Patients

Abstract: This study demonstrated that at a paediatric isolation ward the incidence of ADRs caused by unlicensed or off-label drug use was not significantly more than that caused by the licensed drug use. However, patients treated with unlicensed or off-label drugs were shown to possess a significantly increased risk for developing ADRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
3
16

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(113 citation statements)
references
References 21 publications
10
83
3
16
Order By: Relevance
“…Previous inpatient studies report 27-45% of prescriptions being OLUL, 3,75,76 and two previous community-based studies report 7% and 43% of prescriptions being off-label; 77,78 compare this to 28% of prescriptions in this study. With the exception of Neubert et al 75 these studies all found an increased ADR risk associated with OLUL medicine use.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous inpatient studies report 27-45% of prescriptions being OLUL, 3,75,76 and two previous community-based studies report 7% and 43% of prescriptions being off-label; 77,78 compare this to 28% of prescriptions in this study. With the exception of Neubert et al 75 these studies all found an increased ADR risk associated with OLUL medicine use.…”
Section: Discussionsupporting
confidence: 55%
“…Previous inpatient studies report 27-45% of prescriptions being OLUL, 3,75,76 and two previous community-based studies report 7% and 43% of prescriptions being off-label; 77,78 compare this to 28% of prescriptions in this study. With the exception of Neubert et al 75 these studies all found an increased ADR risk associated with OLUL medicine use. In this study, OLUL medicines were more likely to be implicated in an ADR than medicines used within the terms of their MA; however, it is important to highlight that 87.2% of ADRs that involved at least one OLUL also involved at least one other medicine; in some cases the OLUL medicine may not have caused the ADR in the absence of an approved medicine.…”
Section: Discussionsupporting
confidence: 55%
“…It is likely that the use of unlicensed or "off label" drug prescriptions is associated with a greater risk of ADRs in the paediatric population [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This practice may bring beneficial results, indicating new ways for scientific research on the standardization of indications and dosages. On the other hand, in addition to lack of therapeutic effect, it can also result in adverse reactions (Di Paolo et al, 2006;Naubert et al, 2004).…”
Section: Off-label Indications and Drug Promotional Practicesmentioning
confidence: 99%
“…This study revealed that most off-label uses happen without scientific support. It is estimated that 23% to 60% of these medications are responsible for adverse reactions in children (Naubert et al, 2004;Patel et al, 2007).…”
Section: Off-label Indications and Drug Promotional Practicesmentioning
confidence: 99%